PENGARUH LEVERAGE, INTENSITAS ASET TETAP, DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK - Eka Ridho Nur Rochmah; Rachmawati Meita Oktaviani (Universitas Sains dan Teknologi Komputer, 2021)
This study aims to determine the effect of leverage, fixed asset intensity, and firm size on tax aggressiveness. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sample of this research was taken using non-probability sampling method with purposive sampling technique and certain criteria. The method used in this research is panel data regression analysis. The results of this study indicate that leverage has a significant positive effect on tax aggressiveness, while the intensity of fixed assets has no effect on tax aggressiveness, and firm size has a significant positive effect on tax aggressiveness. The implications of the results of this study provide input to companies in making decisions to minimize the tax burden paid so that companies can be more aggressive towards taxes.